FinTech the technology driving disruption in the financial services industry - Arjunwadkar, Parag Y. (CRC Press, Taylor & Francis Group, 2018)
Everything that we know about the world of finance is changing before us. Innovation is happening constantly, despite the protests of the traditional financial industry. The change is going to keep coming, the only thing we can do is get on board with it. This book introduces the basics of FinTech and equips readers with the knowledge to get on the cutting edge of the age we live in today. With all the new technology that we have today, it is almost mind-blowing to think about the kind of technology that we will have in another ten years or so.